Evaluating R&D management systems: strengths and weaknesses of universities and government-funded research institutes. (12th October 2009) - Yun, Jin-Hyo Joseph; Kim, Byung-Tae; Schlossstein, Dominik F.
This study was conducted to determine relative areas of improvement in R&D management systems for universities and research institutes in the Republic of Korea. The research was motivated partly by recent efforts of the Ministry of Science and Technology (MOST), Republic of Korea to strengthen the management system of R&D accounts in order to promote efficiency and best practices in handling R&D budgeting and account matters. To this end, MOST introduced a binding certification system that is able to evaluate the ability and skill of government-funded national research institutes and universities under its jurisdiction to manage R&D accounts. The certification system is based on a set of criteria, broken down into 3 categories and 27 subcategories. This study analyses and compares the government-funded research institutes and major universities applying for the certification of R&D accounts, based on all the categories. This study shows that the research institutes boast comparatively better systems for self-audit, the precontrol of R&D accounts, the R&D management organisation, the perfection of R&D management manuals and the items of trial production cost and travel expenditures. On the other hand, the universities are better organised in such aspects as the computerisation of R&D management and the database maintenance of R&D accounts. Both major findings are statistically significant.